Insecurity and fear of crime in Argentina: Crime, media and politics in neoliberal times - Cerruti, Pedro (2016)
The emergence of a punitive approach to social insecurity as a response to the new social question produced by neoliberalism has been described as a global trend. Furthermore, it is a trend that characterizes the increasingly polarized and exclusionist post-industrial societies. In this article, I present a study of the development of these transformations in Argentina, in particular the cultural processes involved in the social construction of “insecurity” as a public problem. Two moments in recent Argentine history are considered: first, the hyperinflationary crisis period of 1989-1990 in which insecurity first emerged as a form of representation of the social consequences of the economic crisis; and, second, Carlos Menem’s second presidency between 1995 and 1999, during which the terminal crisis of neoliberalism occurred and insecurity first appeared as one of the main concerns of the public and as a key issue in political disputes, becoming a priority on the government agenda. Focusing specifically on the political and mass media discourses through which crime and violence were thematized as social problems in the public sphere, this paper analyses the articulation of a discursive formation within which social conflicts caused by the crises of the neoliberal reform were formed as criminal problems that required policing and repressive approaches in order to control them.